Corporate Risk Disclosure in Emerging Economies: A Systematic Literature Review and Future Directions - Wahh, Wong Baan; Khin, Edward Wong Sek; Abdullah, Mazni (Asian Journal of Accounting Perspectives, 2020)
Research aim: Corporate risk disclosure (CRD) has long been regarded as a focal point of corporate communication since adequate disclosure of risk information in the annual report may reduce investors’ uncertainty and assist investors to make sound investment decisions. However, previous reviews of CRD literature have tended to focus on developed economies which may have limited applicability in the emerging markets. The aim of this article is, therefore, to extend reviews of CRD literature to emerging economies. Design/ Methodology/ Approach: This paper concentrated on articles published in international peer-reviewed academic journals. Guided by the review methods recommended by Fink (2010) and Tranfield et al. (2003), a systematic review of the most relevant databases within social sciences was performed. Research findings: Valuable evidence emerge from the review. The authors found that most prior risk disclosure studies have focused on the developed economies and that similar research within the context of emerging countries remains under-represented. The literature review also suggests that CRD studies have mainly adopted content analysis to examine the scope of voluntary disclosure practices. The findings show that agency theory remains the most dominant theory to explain the managerial attitudes towards risk disclosure practices. More interestingly, the authors found that rather than solely relying on a single theory alone to explain the phenomenon of CRD, more studies are incorporating multiple theoretical lenses to examine CRD given the diverse nature of voluntary risk reporting. Theoretical contribution/ Originality: The paper adds to the limited number of systematic literature reviews relating to CRD in both developed and emerging economies. Practitioner/ Policy implication: By providing an important snapshot through an integrated and synthesised overview of the current body of knowledge in the field of CRD, the findings may generate new insights to regulatory bodies and standard setters to refine policies on voluntary disclosure practices, conduct more effective monitoring on the level of information transparency among listed companies. Keywords: Voluntary disclosure, Risk Reporting, Emerging economies, Theoretical Perspectives Type of article: Literature review JEL Classification: M40, M41, G30